Employee Engagement and Innovative Work Behavior Among Chinese Millennials: Mediating and Moderating Role of Work-Life Balance and Psychological Empowerment - Ali, Hazem; Li, Min; Qiu, Xunmin (Frontiers in Psychology, 2022)
Given the ever-changing business environment, organizations are forced to consider innovation as an essential perquisite to enhance their efficiency, productivity and sustainability. In this regard, organizations pay increased attention to enhancing employees’ engagement (EE) and stimulating their innovative work behaviors (IWBs). Research emphasize the importance of employees’ IWBs in achieving competitive advantages organizational sustainability. In this research, we address the question of whether employee engagement leads to stimulating IWBs of Chinese millennial workforce in service industries. In addition, we explore the potential mediating effect of work-life balance (WLB) and the moderating influence of psychological empowerment (PE) on the relationship between EE and IWBs. Self-administered questionnaires were used to collect data from 372 Chinese senior employees working in IT, trade, real-estate, financial, telecommunication industries. Our empirical findings showed that highly engaged employees are most likely to exhibit IWBs and maintain a WLB. In addition, the relationship between EE and IWB was partially mediated by WLB. Moreover, the interaction between EE and PE was found to strengthen employees’ IWBs. Our study contributes to understanding the importance of EE as an essential perquisite for millennials’ IWBs and provide new insights for service organizations to encourage employees’ IWBs. This study contributes to human resource management field by offering valuable implications vis-à-vis how service organizations operating in a turbulent business environment stimulate the IWBs of their millennial workforce.